The disaster recovery handbook : a step-by-step plan to ensure business continuity and protect vital operations, facilities, and assets - Wallace, Michael, 1960-; Webber, Lawrence (AMACOM, 2018)
This thoroughly updated third edition provides readers with clear and comprehensive instructions for assessing risk; documenting recovery procedures; assembling a disaster team; testing and debugging every step; protecting material resources; and safeguarding vital records. The Disaster Recovery Handbook helps plan for every contingency, ensuring any company is responsible, ready, and resilient.
Includes index.
Keywords: Emergency management -- Handbooks, manuals, etc.; Crisis management -- Handbooks, manuals, etc.; Computer security -- Handbooks, manuals, etc.; Data protection -- Handbooks, manuals, etc.; Data recovery (Computer science) -- Planning -- Handbooks, manuals, etc.; Business planning -- Handbooks, manuals, etc.; elektronické knihy; electronic books